2021
DOI: 10.15252/embj.2020107586
|View full text |Cite
|
Sign up to set email alerts
|

A CRMP4‐dependent retrograde axon‐to‐soma death signal in amyotrophic lateral sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal non‐cell‐autonomous neurodegenerative disease characterized by the loss of motor neurons (MNs). Mutations in CRMP4 are associated with ALS in patients, and elevated levels of CRMP4 are suggested to affect MN health in the SOD1G93A‐ALS mouse model. However, the mechanism by which CRMP4 mediates toxicity in ALS MNs is poorly understood. Here, by using tissue from human patients with sporadic ALS, MNs derived from C9orf72‐mutant patients, and the SOD1G93A‐ALS mouse m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 81 publications
0
12
0
Order By: Relevance
“…Our analysis on A. nidulans diploids has shown that the kinA K895 * or the kinA (1-894) -GFP allele is also a gain-of-function mutation that partially affects dynein-mediated early endosome transport in the presence of a wild-type copy of kinA (Supplemental Figure 2). As dynein defects have been linked to ALS (Chevalier-Larsen and Holzbaur, 2006; Gershoni-Emek et al, 2016; Hafezparast et al, 2003; Ikenaka et al, 2013; Kieran et al, 2005; LaMonte et al, 2002; Maimon et al, 2021; Mentis et al, 2022; Münch et al, 2004; Stavoe and Holzbaur, 2019; Ström et al, 2008), it is likely that a partial defect in dynein function contributes to ALS caused by the gain-of-function mutations in KIF5A. Future studies will be needed to test this idea.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our analysis on A. nidulans diploids has shown that the kinA K895 * or the kinA (1-894) -GFP allele is also a gain-of-function mutation that partially affects dynein-mediated early endosome transport in the presence of a wild-type copy of kinA (Supplemental Figure 2). As dynein defects have been linked to ALS (Chevalier-Larsen and Holzbaur, 2006; Gershoni-Emek et al, 2016; Hafezparast et al, 2003; Ikenaka et al, 2013; Kieran et al, 2005; LaMonte et al, 2002; Maimon et al, 2021; Mentis et al, 2022; Münch et al, 2004; Stavoe and Holzbaur, 2019; Ström et al, 2008), it is likely that a partial defect in dynein function contributes to ALS caused by the gain-of-function mutations in KIF5A. Future studies will be needed to test this idea.…”
Section: Resultsmentioning
confidence: 99%
“…Cytoplasmic dynein is the minus-end-directed microtubule motor, and defects in dynein and/or its regulator dynactin have been implicated in ALS (Chevalier-Larsen and Holzbaur, 2006; LaMonte et al, 2002; Maimon et al, 2021; Münch et al, 2004). Some vesicular cargos bind both dynein and kinesin-1 via the same cargo adapter (Cox and Spradling, 2006; Fenton et al, 2021; Fu and Holzbaur, 2014)(Canty et al, 2021, bioRxiv; Celestino et al, 2021, bioRxiv), and in this case, loss of kinesin-1 autoinhibition may help overcome the force of dynein to change cargo distribution (Baron et al, 2022; Kelliher et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Sema3A-CRMPs signaling has been suggested to be involved in ALS pathogenesis because Sema3A is upregulated in the motor cortex of ALS patients and the terminal Schwann cell adjacent to neuromuscular junctions (NMJs) in SOD1 G93A mice ( De Winter et al, 2006 ; Körner et al, 2016 ). Moreover, elevation of both Crmp4 and Crmp4-dynein complex leads to neuronal death in ALS model mice ( Duplan et al, 2010 ; Maimon et al, 2021 ) while the inhibition of Crmp2 phosphorylation ameliorates the motor phenotype of SOD1 G93A mice ( Numata-Uematsu et al, 2019 ). However, it remains uncertain whether CRMP1 is involved in the pathomechanism of ALS.…”
Section: Introductionmentioning
confidence: 99%
“…ALS, CMTs and others). We and others have over the years developed several stem cell in vitro platforms for MNs combining stem cells, bioengineering, and imaging 10,1518 to faithfully recapitulate their biology and mechanisms of disease in ALS. However, these in vitro models fail to recapitulate the length of motor axons, which is in most cases the used culture systems generate cells with axons ranging from 1-200um 19 to at most 1 millimeter 20,21 or do not provide a controlled environment for measuring axonal length, lacking the modelling of potential biophysical constraints which long axons provide in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…ALS, CMTs and others). We and others have over the years developed several stem cell in vitro platforms for MNs combining stem cells, bioengineering, and imaging 10,[15][16][17][18] to faithfully recapitulate their biology and mechanisms of disease in ALS.…”
Section: Introductionmentioning
confidence: 99%